The Effect of Meditation Therapy On Reducing Public Stress Levels Due To The Covid-19 Pandemic At Mojosongo Surakarta (Journal of Vocational and Career Education, 2022)
Almost all countries are experiencing an outbreak of the corona virus or covid-19. The emergence of a pandemic causes stress at various levels of society. Stress is a mental disorder faced by a person due to pressure. One of the effective therapies to reduce the level of stress experienced by the community is Mindfulness Meditation. Mindfulness meditation has been shown to significantly have an effect on reducing stress levels experienced by people due to the Covid-19 pandemic. This study aims to determine the effect of Mindfulness Meditation therapy on reducing stress levels. This study uses the Pre Experiment technique with One Group Pre and Post Design. The sample in this study was the people of Karanganyar RT 3 RW 11 Palur. The number of samples used was 50 patients. The sampling technique used was purposive sampling technique. After statistical testing using Wilcoxon, the results obtained a significance of 0.000 (p value 0.05). There is an effect of Mindfulness meditation therapy on reducing stress levels in the community due to the pandemic in Mojosongo Village, Surakarta.